VD_FINDINFO HC / 2014 / 480 vom 26. Juni 2014 - VD Tribunal cantonal (2014)
EXPULSION DE LOCATAIRE, DÉCISION D'IRRECEVABILITÉ, MOTIVATION DE LA DEMANDE | 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 311 al. 1 CPC (CH)